(untitled) (Research, Society and Development, 2025)
Cerebrovascular accident (CVA) is one of the main causes of morbidity and mortality in the world, requiring quick and well-structured responses to address it. Objective: to develop and implement communication management tools to optimize the organization of the stroke care line, aiming at improving clinical outcomes, care efficiency, cost reduction, and strengthening interdisciplinary work. Methodology: the study was conducted using exploratory methods, supported by the assumptions of cross-sectional action research, with a quantitative and qualitative approach, analyzing indicators such as response time in care, clinical outcomes, and quality of interdisciplinary communication. Results: the centralization of information in the application will minimize errors related to communication and facilitate clinical decision-making, aligning with national and international patient safety guidelines. Conclusion: the integration promoted by the application aims to improve the quality of interdisciplinary work, contributing to the continuity of care, from the acute phase to rehabilitation.